The Development of Hydropower Resources at American Watershed Scale and Its Enlightenment to China - Chen, Liang; Sui, Xin; Dong, Zhaokai; Wu, Sainan; Zhou, Hong (Journal of Environmental Accounting and Management, 2026)
Hydropower resources are priority areas of energy construction in various countries throughout the world, and are also important measures for China by which to ensure the energy supply and achieve the development goal of non-fossil energy. Developed countries, in particular the United States, have rich experience in the development and construction of hydropower resources. Therefore, understanding the experience of the United States in the development of hydropower resources bears important enlightenment to the development of hydropower resources in China. This paper gives a systematic review of the survey data previously and newly released by the US Department of Energy; based on this, analyzes the development status of hydropower resources of all watersheds in the United States and the development potential of newly increased hydropower resources; and recounts the development level of hydropower resources at American watershed. At the same time, in consideration to the implementation of efficiency increase and capacity expansion planning in the United States in the future, this paper further predicts the development level of hydropower resources at all watersheds in the United States after this planning has been implemented. Finally, the paper summarizes the experience of the United States in the development of hydropower resources, along with its enlightenment to the development of hydropower resources of China. This study shows that electric construction strategies for the priority development of hydropower, introduction of key constraints to assess the development potential of hydropower resources, and efficiency increase and capacity expansion transformation to intensify the hydropower development are powerful guarantees of hydropower development in the United States, and these also provide important reference value for developing the hydropower resources of China.